Encyclopedia of management (Gale virtual reference library, 2009)
Covers numerous topics in management theories and applications, such as aggregate planning, benchmarking, logistics, diversification strategy, non-traditional work arrangements, performance measurement, productivity measures, supply chain management, and much more.